Iron-nitrogen-carbon catalyst as well as preparation method and application thereof

By introducing 1,4-terephthalene as a molecular template in the preparation process of Fe-N-C catalyst to form a Fe-N-C catalyst with a graded porous structure, the problems of insufficient porosity of the existing catalyst and limited mass transfer pathway are solved, and the efficient ORR activity and stability of the catalyst are achieved.

CN119920918AActive Publication Date: 2025-05-02HAINAN TROPICAL OCEAN UNIV +1

Patent Information

Application Number
CN202510400976.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The microporous structure generated by existing ZIF8-derived Fe-N-C catalysts during carbonization leads to insufficient porosity and limited mass transfer pathways, and rapid decline in catalytic performance.

Method used

By introducing 1,4-terephthalene as a molecular template, its molecular structure is used to promote the aggregation of ZIF8 precursors and the formation of pore structures during carbonization, a Fe-N-C catalyst with a graded porous structure was prepared.

Benefits of technology

The obtained Fe-N-C catalyst has excellent ORR activity and stability, improved mass transfer efficiency, high defect density, and increased pyridine N and graphite N content. It is suitable for zinc air batteries and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920918A_ABST
    Figure CN119920918A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ORR catalyst preparation, in particular to an iron-nitrogen-carbon catalyst and a preparation method and application thereof. The invention provides a preparation method of an iron-nitrogen-carbon catalyst, which is characterized by comprising the following steps: dispersing zinc salt and ferrite in methanol to obtain a mixed solution A; the preparation method comprises the following steps: dispersing 2-methylimidazole and 1, 4-terephthalonitrile in methanol under a heating condition to obtain a mixed solution B; stirring and mixing the mixed solution A and the mixed solution B to obtain precursor powder, and calcining the precursor powder in an inert atmosphere to obtain the iron-nitrogen-carbon catalyst with the hierarchical porous structure. The invention provides a novel preparation method for preparing the iron-nitrogen-carbon catalyst with the hierarchical pore structure, and the iron-nitrogen-carbon catalyst with the hierarchical pore structure is prepared by introducing a 1, 4-terephthalonitrile molecular template.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ORR catalyst preparation, and in particular to an iron-nitrogen-carbon catalyst and a preparation method and application thereof. Background Art

[0002] Oxygen reduction reaction (ORR), as an important electrochemical process related to energy devices such as fuel cells and metal-air batteries, has attracted extensive attention in the past few decades. It is well known that platinum-based electrocatalysts can perfectly solve the 4e - The ORR reaction kinetics are slow, but its high price, scarce resources, and easy poisoning make it difficult to apply on a large scale. Therefore, there is an urgent need to develop efficient, durable and non-precious electrocatalysts, not only to replace the platinum-based materials in ORR, but also to achieve a breakthrough in large-scale problems.

[0003] Transition metal-nitrogen-carbon (MNC, M=Fe, Co, Mn, etc.) catalysts exhibit excellent electrocatalytic performance and good ORR stability. Notably, iron-nitrogen-carbon (Fe-NC) catalysts, especially those based on ZIF8 zeolite, have emerged as the most promising MNC-based ORR catalysts due to their high electrochemical potential and low reaction energy barrier. However, the carbonization process of ZIF8-derived Fe-NC catalysts usually produces microporous structures characterized by insufficient porosity and limited mass transfer pathways, resulting in a rapid decrease in catalytic performance during the reaction. Therefore, it is imperative to develop new and efficient Fe-NC catalysts with hierarchical pore structures to improve their catalytic activity.

[0004] The strategic design of hierarchical pore structures is considered to be an efficient method to enhance catalyst mass transfer and optimize the utilization of active sites. Specifically, micropores are crucial for exposing catalytic active sites, mesopores improve molecular mass efficiency, and macropores significantly improve mass transfer efficiency. Xie (Xie Y, Yu X, Jin Z, et al. Dual-template strategy synthesis ofhierarchically porous electrocatalysts for oxygen reduction reaction [J]. Advanced Sensor and Energy Materials, 2022, 1(2): 100006.) et al. used silica and sodium chloride as templates to create mesopores and synthesized (FeCo)HPNC@NaCl catalysts, which exhibited ORR activity comparable to commercial Pt / C under acidic conditions. Zhu C, Shi Q, Xu B, et al. Hierarchically Porous M-NC (M = Co and Fe) Single-Atom Electrocatalysts with Robust MNx Active Moieties Enable Enhanced ORR Performance [J]. Advanced Energy Materials, 2018, 8(29): 1801956. et al. used a combination of silica colloid and zinc chloride as a pore-inducing template to synthesize MNC (M = Fe, Co), producing a porous structure and atomically dispersed MNx. 2 active sites, showing excellent activity and stability in ORR performance.

[0005] Therefore, current methods mainly rely on hard template, soft template and hybrid template methods, which lead to complex synthesis procedures, reduced productivity and increased costs, hindering large-scale commercial manufacturing. In addition, the structural integrity and porosity of the synthesized catalysts may be compromised during the template removal process, especially when using environmentally harmful solvents such as hydrofluoric acid and hot alkaline solutions. Summary of the invention

[0006] The present invention provides an iron-nitrogen-carbon catalyst and a preparation method and application thereof. The present invention provides a new scheme for synthesizing an iron-nitrogen-carbon catalyst with a hierarchical pore structure, which is simple and efficient to prepare and can obtain hierarchical pores with a complete structure without relying on harmful reagents; at the same time, the obtained iron-nitrogen-carbon catalyst has excellent ORR activity.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing an iron-nitrogen-carbon catalyst, which is characterized by comprising: S1. zinc salt and ferrous salt are dispersed in methanol to obtain a mixed solution A; under heating conditions, 2-methylimidazole and 1,4-terephthalonitrile are dispersed in methanol to obtain a mixed solution B; S2. Mixed solution A and mixed solution B are stirred and mixed to obtain a precursor powder, and the precursor powder is calcined under an inert atmosphere to obtain an iron-nitrogen-carbon catalyst having a hierarchical porous structure.

[0008] The applicant introduced 1,4-terephthalonitrile as a molecular template in the early preparation process of ZIF8 materials, which is conducive to the aggregation of smaller ZIF8 precursors into larger catalyst particles. This process promotes the aggregation of single catalytic molecules in the pyrolysis stage, helps to establish a more stable solid catalytic interface, which is manifested in the improvement of hierarchical porous structure and graphitization level, and finally obtains an iron-nitrogen-carbon catalyst with a hierarchical porous structure.

[0009] Preferably, the zinc salt is zinc nitrate and the ferrous salt is ferrous sulfate.

[0010] Preferably, in S1, the molar ratio of zinc in the zinc salt, iron in the ferrous salt, 2-methylimidazole and 1,4-terephthalonitrile is 5:0.2:(40-42):(0.3-2).

[0011] More preferably, the molar ratio of zinc in the zinc salt, iron in the ferrous salt, 2-methylimidazole and 1,4-terephthalonitrile is 5:0.2:(40-42):(0.7-1).

[0012] Preferably, in S1, the heating condition is: heating to 60-70° C. in an oil bath.

[0013] Preferably, in S2, the stirring and mixing time is 6 to 8 h, and after stirring and mixing, the precursor powder is dried in vacuum at 60 to 80° C. for 12 to 24 h to obtain the precursor powder.

[0014] Preferably, in S2, the inert atmosphere is nitrogen and / or argon.

[0015] Preferably, in S2, the calcination method is: heating to 180-200° C. and keeping the temperature for 2-3 h, and then continuing to heating to 800-900° C. and keeping the temperature for 2-3 h.

[0016] Preferably, the temperature is increased to 180-200° C. at 8-10° C. / min, and then continued to be increased to 800-900° C. at 3-5° C. / min.

[0017] Further preferably, in S2, the calcination method is: heating to 200°C at 10°C / min and keeping it at that temperature for 2 h, and then heating to 900°C at 5°C / min and keeping it at that temperature for 2 h.

[0018] The present invention also provides an iron-nitrogen-carbon catalyst having a hierarchical porous structure of micropores and mesopores, a defect density of ≥0.97, and a particle size of 550-650 nm.

[0019] Preferably, the specific surface area of ​​the iron-nitrogen-carbon catalyst is 600-800 m 2 / g, and the mesopore area is 420~440 m 2 / g, pore volume is 1.0~1.5 cm 3 / g.

[0020] The iron-nitrogen-carbon catalyst prepared by the above method has a hierarchical porous structure. Combined with Raman, XPS and other characterization results, it is proved that the obtained iron-nitrogen-carbon catalyst has a hierarchical porous structure to help improve the mass transfer efficiency of the catalyst active sites, and its high defect density can promote the adsorption of oxygen; in addition, the emergence of the hierarchical porous structure helps to enhance the content of pyridine N and graphite N, and the iron-nitrogen-carbon catalyst finally obtained has excellent ORR activity.

[0021] The present invention also provides a zinc-air battery, which uses the iron-nitrogen-carbon catalyst as a catalyst material for a cathode.

[0022] The use of iron-nitrogen-carbon catalysts with hierarchical porous structures can effectively help zinc-air batteries improve open circuit voltage, specific capacity, stability and other performance. It is proved that iron-nitrogen-carbon catalysts with hierarchical porous structures have significant battery performance and have broad application prospects in zinc-air fuel cells.

[0023] Therefore, the present invention has the following beneficial effects: (1) The present invention provides a new preparation method for preparing an iron-nitrogen-carbon catalyst with a hierarchical pore structure, wherein the iron-nitrogen-carbon catalyst with a hierarchical pore structure is prepared by introducing a 1,4-terephthalonitrile molecular template.

[0024] (2) The iron-nitrogen-carbon catalyst provided by the present invention has a hierarchical porous structure, which can help improve the mass transfer efficiency of the active sites of the catalyst, and its high defect density can promote the adsorption of oxygen; in addition, the emergence of the hierarchical porous structure helps to enhance the content of pyridine N and graphite N, and the finally obtained iron-nitrogen-carbon catalyst has excellent ORR activity.

[0025] (3) The zinc-air battery provided by the present invention uses an iron-nitrogen-carbon catalyst as a cathode catalyst, which significantly improves the open circuit voltage, specific capacity, stability and other properties of the battery, proving that the iron-nitrogen-carbon catalyst can be widely used as a catalyst source for zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Fe-N / C 1,4-DB Schematic diagram of the preparation of a series of catalysts; Figure 2 The scanning electron microscope image of Fe-N / C series catalysts, where a is Fe-ZIF8 1,4-DB-0.1 SEM images of b and Fe-N / C 1,4-DB-0.1 SEM images of Fe-N / C at different magnifications. 1,4-DB-0.1 HRTEM image of Fe-N / C 1,4-DB-0.1 Mapping diagram; Figure 3 Fe-ZIF8 and Fe-ZIF8 / 1,4-DB-0.1 FT-IR spectrum of Figure 4 Fe-N / C 1.4-DB-Y Performance characterization diagrams of a series of catalysts, where a is the nitrogen adsorption-desorption isotherm curve, b is the pore size distribution curve, c is the XRD spectrum, d is the Raman spectrum, e is the high-resolution XPS spectrum of N 1s, and f is the high-resolution XPS spectrum of Fe 2p; Figure 5 Fe-N / C 1,2-DB-0.1 Nitrogen adsorption-desorption isotherm curve of catalyst; Figure 6 Fe-N / C 1,2-DB-0.1 Pore ​​size distribution curve of the catalyst; Figure 7 Fe-N / C 1.4-DB-Y XPS spectra of a series of catalysts; Figure 8 Fe-N / C 1,4-DB-0.1 The N content variation of the catalyst; Fig. 9 Fe-N / C 1,2-DB-0.1 XPS spectrum of the catalyst; Fig.10 The electrochemical performance diagram of the catalyst, wherein a is the cyclic voltammetry curve, b is the linear sweep voltammetry curve, c is the Tafel slope diagram, d is the electron transfer number and hydrogen peroxide yield, e is the chronoamperometric response, and f is the current-time chronoamperometric response; Fig.11 Fe-N / C 1.4-DB-Y ORR performance diagram of a series of catalysts; Fig.12 Fe-N / C 1,2-DB-0.1 Linear sweep voltammetry curves of the catalyst; Fig.13 Fe-N / C 1,3-DB-0.1 Linear sweep voltammetry curves of the catalyst; Fig.14 The performance test diagram of zinc-air battery, where a is the schematic diagram of zinc-air battery device, b is the open circuit voltage curve, c is the polarization curve and power density, and d is the Fe-N / C 1,2-DB-0.1 Photo of the red LED lit by the zinc-air battery with catalyst, e is the full discharge curve and its corresponding specific capacity, and f is the constant current discharge curve under different current densities. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0028] In this section, FeSO 4 7H 2 O, 2-methylimidazole (AR 98%), methanol (AR 99.5%), 1,4-terephthalonitrile (AR 98%), 1,4-phthalonitrile (AR 98%), and 1,4-isophthalonitrile (AR 98%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Zn(NO 3 ) 2 6H 2 O was purchased from Sinopharm Chemical Reagent Co., Ltd.; Pt / C catalyst (20%) was purchased from Suzhou Sinero Technology Co., Ltd.; Nafion D520 (5%) was purchased from DuPont China Holdings Co., Ltd. All reagents used in this section were not further purified.

[0029] [Example] Example 1 S1.Zn(NO 3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) and 1,4-terephthalonitrile (0.10 g, 0.78 mmol) were dispersed in 30 mL of methanol, and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0030] S2. Add the mixed solution A to the mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum oven at 80°C for 12 h to obtain Fe-ZIF8 / 1,4-DB-0.1 Precursor powder.

[0031] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1 The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, then continued to rise to 900°C at 5°C / min and kept at this temperature for 2 h. Fe-N / C 1,4-DB-0.1 catalyst.

[0032] Example 2 S1.Zn(NO 3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2 O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) and 1,4-terephthalonitrile (0.05 g, 0.39 mmol) were dispersed in 30 mL of methanol, and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0033] S2. Add the mixed solution A to the mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum oven at 80°C for 12 h to obtain Fe-ZIF8 / 1,4-DB-0.05 Precursor powder.

[0034] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1 The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, then continued to rise to 900°C at 5°C / min and kept at this temperature for 2 h. Fe-N / C 1,4-DB-0.05 catalyst.

[0035] Example 3 S1.Zn(NO3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2 O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) and 1,4-terephthalonitrile (0.25 g, 1.95 mmol) were dispersed in 30 mL of methanol and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0036] S2. Add the mixed solution A to the mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum oven at 80°C for 12 h to obtain Fe-ZIF8 / 1,4-DB-0.25 Precursor powder.

[0037] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1 The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, then continued to rise to 900°C at 5°C / min and kept at this temperature for 2 h. Fe-N / C 1,4-DB-0.25 catalyst.

[0038] Comparative Example 1 S1.Zn(NO 3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2 O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) was dispersed in 30 mL of methanol, and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0039] S2. Add mixed solution A to mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum drying oven at 80°C for 12 h to obtain Fe-ZIF8 precursor powder.

[0040] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1 The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, and then continued to be raised to 900°C at 5°C / min and kept at this temperature for 2 h. The Fe-N / C catalyst was obtained by calcination.

[0041] Comparative Example 2 S1.Zn(NO 3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2 O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) and 1,2-phthalonitrile (0.10 g, 0.78 mmol) were dispersed in 30 mL of methanol, and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0042] S2. Add the mixed solution A to the mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum oven at 80°C for 12 h to obtain Fe-ZIF8 / 1,2-DB-0.1 Precursor powder.

[0043] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1 The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, then continued to rise to 900°C at 5°C / min and kept at this temperature for 2 h. Fe-N / C 1,2-DB-0.1 catalyst.

[0044] Comparative Example 3 S1.Zn(NO 3 ) 2 6H 2 O (1.5024 g, 5 mmol), FeSO 4 7H 2 O (0.0561 g, 0.2 mmol) was dispersed in 30 mL of methanol to obtain a mixed solution A. 2-Methylimidazole (3.3510 g, 40.8 mmol) and 1,3-isophthalonitrile (0.10 g, 0.78 mmol) were dispersed in 30 mL of methanol, and then stirred and mixed in an oil bath at 60°C to obtain a mixed solution B.

[0045] S2. Add the mixed solution A to the mixed solution B and stir for 6 h. Centrifuge to obtain a red-yellow precipitate, then wash it three times with methanol to remove impurities in the precipitate, and dry it in a vacuum oven at 80°C for 12 h to obtain Fe-ZIF8 / 1,3-DB-0.1 Precursor powder.

[0046] S3. Under nitrogen atmosphere, Fe-ZIF8 / 1,4-DB-0.1The precursor powder was pyrolyzed in a tube furnace. The temperature was first raised to 200°C at 10°C / min and kept at this temperature for 2 h, then continued to rise to 900°C at 5°C / min and kept at this temperature for 2 h. Fe-N / C 1,3-DB-0.1 catalyst.

[0047]

Performance test

[0048] Furthermore, the Fe-N / C 1,4-DB-0.1 The catalyst was characterized by scanning electron microscopy and transmission electron microscopy. Figure 2 shown. Figure 2 b in Fe-ZIF8 / 1,4-DB-0.1 The SEM image of the precursor powder shows that Fe-ZIF8 / 1,4-DB-0.1 The precursor powder has a regular hexahedral structure and a particle size of about 250 nm. 1,4-DB-0.1 The precursor powder was calcined and carbonized to obtain Fe-N / C 1,4-DB-0.1 The catalyst has a structure such as Figure 2 As shown in Figure c, after carbonization, its surface changes from a smooth hexahedral structure to a rough spherical structure, and the particle size increases to 600 nm. 1,4-DB-0.1 After the catalyst was characterized by transmission electron microscopy, it was found that the Fe-N / C 1,4-DB-0.1 The catalyst has an obvious porous structure, which can explain the increase in the particle size of the catalyst particles after carbonization because of the appearance of a loose porous structure.

[0049] Figure 2 g in Fe-N / C 1,4-DB-0.1 Catalyst mapping diagram, it can be observed that C, N, and Fe are evenly distributed in the Fe-N / C 1,4-DB-0.1 The results of FT-IR spectrum show that C and N have successfully entered the framework of ZIF8, and the basic framework of ZIF8 is retained after carbonization, while C and N have successfully doped into Fe-N / C 1,4-DB-0.1 In catalyst.

[0050] 2. Microstructure Characterization The nitrogen physical adsorption technology was used to analyze the Fe-N / C and Fe-N / C 1.4-DB-Y (Y=0.05, 0.1, 0.25) Catalyst, Fe-N / C 1.2-DB-0.1 and Fe-N / C 1.3-DB-0.1 The specific surface area and pore size of Figure 4 a in Figure 4 b in Figure 5 and Figure 6 shown.

[0051] Figure 4 a in Fe-N / C and Fe-N / C 1.4-DB-Y (Y=0.05, 0.1, 0.25) Nitrogen adsorption-desorption isotherm curves of the catalysts show that: all Fe-N / C 1.4-DB-Y The catalysts all showed micropores and mesopores. 2 Pressure (P / P 0 = 0.4-0.95), the presence of micropores leads to an obvious hysteresis curve. On the contrary, the Fe-N / C catalyst has a 2 Pressure (P / P 0 =0-0.015) shows a type IV isotherm and no mesoporous structure appears. Figure 4 b in Fe-N / C and Fe-N / C 1.4-DB-Y (Y=0.05, 0.1, 0.25) The pore size distribution of the catalyst, combined with the specific surface area data in Table 1, shows that: Fe-N / C 1.4-DB-Y0.1 Catalyst specific surface area (762 m 2 / g) and the highest pore volume (1.24 cm 3 / g), mesopore area (430.64 m 2 / g) is the largest. After introducing 1,4-terephthalonitrile as a molecular template, Fe-N / C 1.4-DB-Y Compared with Fe-N / C catalyst, the specific surface area, pore volume and mesopore area of ​​the catalyst are improved to varying degrees. This shows that by using 1,4-terephthalonitrile as a molecular template, mesopores can be introduced into ZIF-8, and the change in the pore size structure of the catalyst helps to improve the mass transfer efficiency of the catalyst active sites. Figure 5 and Figure 6 The results showed that 1,2-phthalonitrile with similar structure could not achieve the same effect as 1,4-terephthalonitrile. The Fe-N / C 1,2-DB-0.1 The catalyst does not show a hierarchical structure of micropores and mesopores.

[0052] Table 1 BET result data table

[0053] After obtaining the above internal pore size structure distribution results, the Fe-N / C 1,2-DB-0.1 Catalyst and Fe-N / C 1.4-DB-Y0.1 The catalyst was characterized by XPS. Figure 4 e in Figure 4 f and Figures 7-9 shown.

[0054] like Figure 4 As shown in e in the figure: The Fe 2p spectrum shows characteristic peaks at 710.6 eV and 723.6 eV, corresponding to Fe 2+ (III) and Fe 2+ (II). In addition, the peaks at 714.6 eV and 727.6 eV are both attributed to Fe 3+ (III) and Fe 3+ (II). Figure 4 f and Figure 7 It shows that pyridinic N (398.5 eV), pyrrolic N (400.3 eV), graphitic N (401.0 eV), and oxidized N (402.7 eV) are present in all samples. It is worth noting that pyridinic N and graphitic N constitute the main peaks of the N 1s XPS spectrum, which not only helps to improve the ORR activity, but also pyridinic N and graphitic N can serve as anchor points for Fe atoms to enhance the stability of the catalytic material. Figure 8 The results show that the incorporation of the molecular template 1,4-terephthalonitrile leads to the Fe-NC / 1,4-DB-0.1 The increased contents of pyridinic N and graphitic N in the catalyst provide a large number of coordination environments that are favorable for the formation of active sites, thereby enhancing the ORR performance of the catalyst.

[0055] Furthermore, for Fe-N / C 1.4-DB-Y (Y=0.05, 0.1, 0.25) The catalysts were characterized by XRD and Raman. Figure 4 c in the figure is the corresponding XRD result, and two significant diffraction peaks (24.2° and 42.3°) can be found, which are both characteristic peaks of carbon. In addition, diffraction peaks of different intensities were found at 35.4°, 53.5° and 56.7°, corresponding to the crystal structure of ferroferric oxide. In summary, with the increase of 1,4-terephthalonitrile content, the diffraction peak intensity of ferroferric oxide gradually decreases. Figure 4 The d in the figure is the Raman spectrum at 1335 cm -1 and 1594 cm -1There are two characteristic peaks at the d-band and g-band. The degree of carbon defects is usually quantified by the ratio of the d-band to the g-band intensities (ID / IG). Comparing the ID / IG values ​​of different catalysts, it is found that Fe-N / C 1,4-DB-0.1 The defect density of (0.98) is greater than that of Fe-N / C (0.96). These results indicate that the incorporation of molecular templates can increase the defect density in the catalyst, thereby promoting the adsorption of oxygen and promoting the ORR performance of the catalyst.

[0056] 3. Electrochemical performance The test method in this section is as follows: it is carried out on a CHI760E electrochemical workstation, with 0.1 M potassium hydroxide solution as the electrolyte, and a three-electrode setup: the counter electrode is a platinum (Pt) electrode, the working electrode is a glassy carbon electrode (GCE) coated with catalyst ink, and the reference electrode is a saturated calomel electrode (SCE). 5 mg of catalyst is dispersed in 1 mL of a solution containing 985 μL of ethanol, 5 μL of 5% Nafion solution, and 10 μL of water, and the catalyst ink is prepared by ultrasonication for at least 30 min.

[0057] Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) experiments were performed in the potential range of 0–1.2 V at a scan rate of 100 mV·s. -1 Before the experiment, the 2 / N 2 The gas was purged for 30 min. Then, the rotation speed was 1600 rpm and the scan rate was 5 mV·s -1 The oxygen reduction polarization curves (ORR polarization curves) of the catalysts were obtained under the conditions of 0~1.2 V vs. RHE. The potential cycle was repeated until a stable linear sweep voltammetry curve was obtained. ORR polarization curves were generated under the same test conditions using a platinum ring electrode with the ring voltage set to 1.5 V (vs RHE). These curves can be used to calculate the electron transfer number and hydrogen peroxide yield using equations (1) and (2).

[0058] (1) (2) In the above formula, n is the number of electron transfers, pieces; HO 2 - is the peroxide yield, %; I d is the current of the glassy carbon disk, A; I r is the current of the platinum ring, A; N is the current collection efficiency of the RRDE platinum ring (N = 0.37).

[0059] The electrocatalytic stability was evaluated by the constant current (IT) method for oxygen reduction reaction. A constant voltage of 0.8 V (vs RHE) was applied to the catalyst-loaded glassy carbon electrode in an oxygen-saturated 0.1 M potassium hydroxide solution. 5000 cycles with a scan rate of 50 mV·s -1 Cyclic voltammogram curves were obtained to induce catalyst aging.

[0060] The Fe-N / C 1,4-DB-0.1 ORR performance of the catalysts. A comparative analysis of Fe-N / C and Pt / C catalysts was performed. All tested potentials were calibrated to a reversible hydrogen electrode (RHE). Fig.11 and Fig.10 a in the figure is the cyclic voltammetry curve of Fe-N / C doped with 1,4-terephthalonitrile molecular template 1,4-DB-0.1 The catalyst has a large curve area. By adjusting the amount of 1,4-terephthalonitrile added, it was found that when the amount of 1,4-terephthalonitrile was 0.1 g, the Fe-N / C 1,4-DB-0.1 In addition, combined with Fig.11 and Fig.10 From b in the figure, we can see that Fe-N / C 1,4-DB-0.1 The catalyst also has the highest half-potential (E 1 / 2 =0.90 V vs RHE) and the maximum limiting current density. Compared with Fe-N / C (0.85 V vs RHE) and 20 wt% Pt / C (0.86 V vs RHE), Fe-N / C 1,4-DB-0.1 The improvement of the catalyst is very significant. In addition, combined with Fig.11 and Fig.10 The ORR performance data of b in Figure 2 confirm that the addition of 1,4-terephthalonitrile molecular template can effectively improve the ORR activity, which is consistent with the Raman results: it proves that the addition of 1,4-terephthalonitrile molecular template can increase the defect density in the catalyst and promote the adsorption of oxygen, which ultimately manifests as an increase in ORR activity. 1,4-DB-0.1 The structural characteristics of the hierarchical pores in the catalyst are also closely related. The hierarchical pore structure helps improve the mass transfer efficiency of the active sites of the catalyst and helps improve the ORR activity. Fig.12 and Fig.13 When 1,2-phthalonitrile and 1,3-isophthalonitrile were used as molecular templates, their ORR activity was lower than that when 1,4-terephthalonitrile was used. The reason may be that 1,2-phthalonitrile did not have a hierarchical pore structure when used as a molecular template, and it was not an effective template. In addition, the change trend of its N site was different from that of 1,4-terephthalonitrile, and Fe-N x, which ultimately leads to a decrease in ORR activity. When 1,3-isophthalonitrile is used as a molecular template, it shows a direct decrease in ORR activity. It is speculated that it is the same as 1,2-ophthalonitrile, because the lack of a hierarchical pore structure ultimately leads to the ORR activity not being optimal. Therefore, in the selection of molecular templates, the formation of a hierarchical pore structure is the most critical part.

[0061] Furthermore, the kinetic performance of ORR was evaluated using the Tafel slope, and the results are recorded in Fig.10 In the c. It can be seen that Fe-N / C 1,4-DB-0.1 The Tafel slope of is the lowest, indicating that it experiences the lowest overpotential during the ORR catalysis, thus exhibiting fast dynamic characteristics. Fig.10 The d in the figure is the comparison data of the electron transfer number and hydrogen peroxide yield. It is found that Fe-N / C 1,4-DB-0.1 The hydrogen peroxide yield was always less than 3%, while the electron transfer efficiency was about 4.0. These data indicate that in the Fe-N / C 1,4-DB-0.1 In the catalytic oxidation process, the electron transfer mechanism dominates the occurrence of the catalytic reaction.

[0062] Furthermore, the constant current method was used to evaluate the Fe-N / C 1,4-DB-0.1 The cycle stability of Fig.10 Figure e shows that after 50,000 s of cycling, the Fe-N / C 1,4-DB-0.1 The current density of the Fe-N / C catalyst decreased by only 7.5%; the current density of the control catalyst decreased by 31.5%, which showed extremely strong cycle stability. In practical catalytic applications, stability is a key factor affecting the commercial feasibility of catalysts. Another ideal catalyst evaluation parameter is methanol resistance. 1,4-DB-0.1 The methanol resistance test was carried out in 0.1 M KOH with 20 wt% Pt / C, and 1 mL of methanol was injected at 200 s. Fig.10 As shown in Figure f, the catalyst current change of 1,4-terephthalonitrile molecular template is almost invisible, while the current of 20% Pt / C is significantly reduced, indicating that Fe-N / C 1,4-DB-0.1 The catalyst has strong methanol resistance.

[0063] 4. Zinc-air battery Based on the electrochemical performance test results of the above catalysts, Fig.14 A Zn-air battery was assembled to further evaluate the Fe-N / C 1,4-DB-0.1 Potential applications of catalysts in practical battery systems. 1,4-DB-0.1The catalyst was used as cathode catalyst (the electrode carrier was glassy carbon electrode, GCE), platinum (Pt) electrode was used as counter electrode, saturated calomel electrode (SCE) was used as reference electrode, and 6 M potassium hydroxide solution was used as electrolyte to complete the performance test of zinc-air battery.

[0064] observe Fig.14 b and Fig.14 From the c in the figure, we can see that using Fe-N / C 1,4-DB-0.1 The open circuit voltage of the Zn-air battery with the catalyst is 1.467 V and the peak power density is 321 mW cm -2 The zinc-air battery made with Pt / C catalyst has an open circuit voltage of 1.459 V and a peak power density of 221 mW cm -2 By comparison, it can be seen that the use of Fe-N / C 1,4-DB-0.1 After adding the catalyst, the performance of the battery is effectively improved. Fig.14 The figure d in the figure shows the phenomenon of zinc-air battery. It is found that the application of Fe-NC / 1 ,4-DB-0.1 Catalyst zinc-air batteries can easily provide a power source for LEDs. 1,4-DB-0.1 The specific capacity of the zinc-air battery with the catalyst is 807 mAh g -1 , while the Zn-air battery based on Pt / C ZAB is only 715 mAh g -1 . Fig.14 f in the figure is the constant current discharge curve of the zinc-air battery assembled at different current densities. It can be seen that the Fe-NC / 1,4-DB-0.1 The catalyst-assembled Zn-air batteries exhibited stable discharge capacity, maintaining a consistent plateau at each discharge current density.

[0065] The above results show that Fe-NC / 1,4-DB-0.1 The catalyst has remarkable battery performance and has broad application prospects in zinc-air fuel cells.

Claims

1. A method for preparing an iron-nitrogen-carbon catalyst, characterized in that: include: S1. zinc salt and ferrous salt are dispersed in methanol to obtain a mixed solution A; Under heating conditions, 2-methylimidazole and 1,4-terephthalonitrile are dispersed in methanol to obtain a mixed solution B; S2. Mixed solution A and mixed solution B are stirred and mixed to obtain a precursor powder, and the precursor powder is calcined under an inert atmosphere to obtain an iron-nitrogen-carbon catalyst having a hierarchical porous structure.

2. The preparation method according to claim 1, characterized in that In S1, the molar ratio of zinc in the zinc salt, iron in the ferrous salt, 2-methylimidazole and 1,4-terephthalonitrile is 5:0.2:(40-42):(0.3-2).

3. The preparation method according to claim 1, characterized in that: In S1, the heating condition is: heating to 60-70° C. in an oil bath.

4. The preparation method according to claim 1, characterized in that: In S2, the stirring and mixing time is 6 to 8 hours, and after the stirring and mixing, the precursor powder is dried in vacuum at 60 to 80° C. for 12 to 24 hours.

5. The preparation method according to claim 1, characterized in that: In the S2, the inert atmosphere is nitrogen and / or argon.

6. The preparation method according to claim 1 or 5, characterized in that: In S2, the calcination method is: heating to 180-200°C and keeping it for 2-3 hours, and then continuing to heat to 800-900°C and keeping it for 2-3 hours.

7. The preparation method according to claim 6, characterized in that: Raise the temperature to 180~200℃ at 8~10℃ / min, and continue to raise the temperature to 800~900℃ at 3~5℃ / min.

8. The iron-nitrogen-carbon catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The iron-nitrogen-carbon catalyst has a hierarchical porous structure of micropores and mesopores, a defect density of ≥0.97, and a particle size of 550-650 nm.

9. The iron-nitrogen-carbon catalyst according to claim 8, characterized in that The specific surface area of ​​the iron-nitrogen-carbon catalyst is 600-800 m 2 / g, and the mesopore area is 420~440 m 2 / g, pore volume is 1.0~1.5 cm 3 / g.

10. A zinc-air battery, characterized in that: The iron-nitrogen-carbon catalyst according to claim 8 or 9 is used as a catalyst material for the cathode.

Citation Information

Patent Citations

  • Cobalt-nitrogen-doped hierarchical porous catalytic material as well as preparation method and application thereof

    CN113210002A

  • Preparation method of iron-based monatomic catalyst applied to oxygen reduction

    CN114669314A

  • Hollow spherical Fe and N co-doped porous carbon-based catalyst as well as preparation method and application thereof

    CN115224291A

  • Zinc air battery air electrode catalyst and preparation method and application thereof

    CN115548357A

  • Preparation of iron-based nitrogen-doped porous carbon material and application of iron-based nitrogen-doped porous carbon material in zinc-air battery

    CN116239113A

Cited By

  • Iron-nitrogen-carbon catalyst with high iron loading capacity as well as preparation method and application of iron-nitrogen-carbon catalyst

    CN121097107A

  • Iron-nitrogen-carbon catalyst with high iron loading and preparation method and application thereof

    CN121097107B